Resveratrol regulates macrophage recruitment and M1 macrophage polarization and prevents corneal allograft rejection in rats - Xu, Chenjia; Guo, Ruilin; Hou, Chao; Ma, Minglu; Dong, Xiaojuan; Ouyang, Chen; Wu, Jing; Huang, Ting (Frontiers in Medicine, 2023)
Introduction Resveratrol is an immune modulator that can reduce M1 macrophage polarization in vitro. Reducing macrophage recruitment and M1 polarization can prevent corneal allograft rejection (CGR). In this study, rat corneal allograft rejection models were established to explore the effects of resveratrol on CGR and macrophages and the underlying mechanisms after corneal transplantation. Methods Corneal allograft models were established, and 100 mg/kg resveratrol was injected intraperitoneally. The corneal allografts were assessed clinically using the Holland rejection scoring system, anterior segment photography, and anterior segment optical coherence tomography. Corneal macrophages, pro-inflammatory cytokines, and corneal lymphatic vessels were detected using hematoxylin and eosin staining, immunofluorescence staining, and real-time quantitative polymerase chain reaction (qRT-PCR). Dendritic cells (DCs) in cervical lymph nodes were explored using flow cytometry. RNA sequencing experiments were conducted to identify the mechanisms through which resveratrol affected CGR. The results were verified using Simple Western analysis. Pro-inflammatory cytokines by macrophages in vitro were measured using qRT-PCR and enzyme-linked immunosorbent assays. Results Resveratrol significantly prolonged the survival of corneal grafts and reduced graft edema and central corneal thickness. Corneal macrophage recruitment and M1 macrophage polarization decreased significantly after corneal transplantation in the resveratrol group. Resveratrol also reduced pro-inflammatory cytokines in corneal grafts and suppressed the early generation of cornea lymphatic vessels and the recruitment of cornea inflammatory cells 14 days after surgery. Resveratrol decreased the proportion of DCs in ipsilateral cervical lymph nodes. The effect of resveratrol on CGR was related to the phosphatidylinositol 3-kinase/protein kinase-B (PI3K/Akt) pathway. Resveratrol reduced the secretion of pro-inflammatory cytokines by M1 macrophages in vitro. Conclusion Our findings suggest that resveratrol can reduce corneal macrophage recruitment and M1 macrophage polarization after corneal transplantation in rats and prevent CGR. The PI3K/Akt pathway may be an important mechanism that warrants further research.